2013
DOI: 10.1088/0957-4484/24/41/415502
|View full text |Cite
|
Sign up to set email alerts
|

Nanocontainer-based corrosion sensing coating

Abstract: The present paper reports on the development of new sensing active coating on the basis of nanocontainers containing pH-indicating agent. The coating is able to detect active corrosion processes on different metallic substrates. The corrosion detection functionality based on the local colour change in active cathodic zones results from the interaction of hydroxide ions with phenolphthalein encapsulated in mesoporous nanocontainers which function as sensing nanoreactors. The mesoporous silica nanocontainers are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(39 citation statements)
references
References 14 publications
0
37
0
2
Order By: Relevance
“…Strain sensing tests revealed that its electrical resistance increased linearly at relatively low levels of applied strain (e < 18,000 µe) and increased nonlinearly at higher strains (18,000 µe < e < 71,000 µe). On the other hand, Maia et al [6] developed mesoporous silica nanomaterialbased corrosion-sensitive coatings. The corrosion sensitive coatings were fabricated by loading mesoporous silica nanocontainers (Si-NC) with phenolphthalein (PhPh) embedded in transparent epoxy.…”
Section: Introductionmentioning
confidence: 99%
“…Strain sensing tests revealed that its electrical resistance increased linearly at relatively low levels of applied strain (e < 18,000 µe) and increased nonlinearly at higher strains (18,000 µe < e < 71,000 µe). On the other hand, Maia et al [6] developed mesoporous silica nanomaterialbased corrosion-sensitive coatings. The corrosion sensitive coatings were fabricated by loading mesoporous silica nanocontainers (Si-NC) with phenolphthalein (PhPh) embedded in transparent epoxy.…”
Section: Introductionmentioning
confidence: 99%
“…The encapsulation of a phenolphthalein dye as a corrosion sensor in mesoporous silica nanocontainers or multifunctional protective coatings has been reported. The phthalein‐based method is used in next generation corrosion‐sensing coatings and is useful for identifying corrosion degradation at an early stage .…”
Section: Industrial Applications Of Phthalein Dyesmentioning
confidence: 99%
“…Over time, many corrosion sensors or probes based on electrochemical or nonelectrochemical theory have been developed and applied to corrosive environments in industry [112][113][114][115]. One suitable route to prevent the failure of the structure is the using of a corrosion control coating filled with pH-sensitive carriers [60][61][62][116][117][118][119][120][121]. The main cathodic reaction in the presence of oxygen involves the reduction of oxygen with formation of hydroxide ions that lead an increase in the local pH (eq.…”
Section: Ph-sensitive Self-release Microcapsulesmentioning
confidence: 99%
“…Maia et al developed a sensing coating by encapsulating PhPh in silica nanocontainers. The authors discovered that PhPh, instead of being released in to the coating, reacts with the hydroxide anions diffused within the capsule and turns them from colourless to pink [119]. Later, the same authors encapsulated PhPh in polyurea microcapsules dispersed in polyurethane based coating [120].…”
Section: Ph-sensitive Self-release Microcapsulesmentioning
confidence: 99%